Development and evaluation of the hydropower reservoir rule curve for a sustainable water supply - Choi, Youngje; Lee, Eunkyung; Ji, Jungwon; Ahn, Jaehwang; Kim, Taesoon; Yi, Jaeeung (Sustainability (Switzerland), 2020)
The Seoul metropolitan area in the Han River basin is searching for sustainable water supply options after recently experiencing an extreme drought. Building a new reservoir is a common way to alleviate water shortage, but this comes at a great environmental cost. The South Korean government granted permission to add on a water supply function for the Hwacheon Reservoir, the largest hydropower reservoir in Korea, for the first time in the history. This study develops a new rule curve for the Hwacheon Reservoir to supply water and generate energy at the same time, considering the status of other reservoirs in the Han River basin. The simulation model uses two scenarios, with scenario 1 simulating historic operation and scenario 2 applying the deficit supply method. The new rule curve was formulated based on the results from scenario 2. Time-based and volumetric reliability increased by 33% and 4%, respectively, and resiliency more than doubled compared to the historic reservoir operation. This is the first case study in South Korea that demonstrates how to successfully integrate a water supply function into an existing hydropower reservoir. This study can be applied and extended to other river basins in an attempt to alleviate water shortages by adding new functions to existing reservoirs.
Keywords: Deficit supply method; Hydropower reservoir; Rule curve; Sustainable water supply